Effects of a stress management program on stress and sleep quality of nursing students - Somprasert, Chitralada; Pongpaew, Warunee; Anansupamongkol, Duangthip; Prompibal , Narumol (Thai Journal of Nursing, 2022)
The purpose of this quasi-experimental research was to study effects of a stress management program on stress and sleep quality of nursing students. A sample of 50 nursing freshmen from Faculty of Nursing Science, Kasem Bundit University, was purposively selected and equally divided into the experiment and control groups using a simple random method. The research tools consisted of a stress management program based on the concept of Lazarus and Folkman, a Thai stress test and Thai version-Pittsburgh sleep quality index. Data were analyzed by descriptive statistics and t-test. The research findings were as follows. After receiving the stress management program, nursing students in the experimental group had significantly lower stress than the pre-experiment (t = 2.449) and the control group (t = 3.227) at p < .05, but their sleep quality had no significant difference from the pre-experiment and the control group.